Continuous Glucose Monitoring: Changing Diabetes Behavior in Real Time and Retrospectively - Block, Jennifer M. (Diabetes Technology Society, 2008)
Results of both the Diabetes Control and Complications Trial and the United Kingdom Prospective Diabetes Studies supported the role of tight glucose control in reducing long-term complications of diabetes. There is further evidence that glycemic variability may be better correlated with the risk for complications than sustained hyperglycemia. These studies reinforce the need to work toward improved glucose control with minimal variability in patients with diabetes. Continuous glucose monitoring technology offers a means of obtaining a more complete picture of glucose patterns and can be used to aid in identifying trends in glycemic variability, especially overnight and after meals when blood glucose testing is not usually performed. Increased access to retrospective trends, the addition of real-time glucose alarms, and prospective trend data can be advantageous in motivating and evaluating behavior change.